Knowledge and practice towards premenstrual syndrome among undergraduate students in health campus Universiti Sains Malaysia - Min, Chua Min (Universiti Sains Malaysia, 2023)
Premenstrual syndrome (PMS) is a prevalent menstrual disorder among women of reproductive age that is significant enough to affect their daily activities and quality of life. A cross-sectional study design was carried out to study the knowledge about PMS and practice towards relieving PMS among undergraduate students in Health Campus Universiti Sains Malaysia (USM). 234 undergraduate students in Health Campus USM were selected randomly to participate in this study. The data was collected quantitatively and was analysed using SPSS statistical software. The findings showed that 62.8% of respondents had a low level of knowledge about PMS, 34.6% had a medium level of knowledge about PMS, and only 2.6% had a high level of knowledge. The practices employed by respondents in relieving PMS were also studied and arranged in decreasing order as rest (95.7%), warm drinks (85.5%), do nothing (60.3%), exercise (53.4%), warm bathing (49.6%), painkillers (46.6%), vitamin supplements (33.3%), traditional remedies (27.4%), antidepressants (6.4%), and homeopathic medications (5.1%). Pearson Chi-square test found that there is a significant association between level of knowledge about PMS and the practice of painkillers (p = 0.016). Besides, there is also a significant association between level of knowledge about PMS and the practice of warm bathing (p = 0.023). In conclusion, undergraduate students need more comprehensive education about PMS to provide better support and care to other individuals, subsequently enhancing the well-being and quality of life of the community as a whole.